Changing trends in the epidemiology of hip fracture in Spain. - Azagra, R; López-Expósito, F; Martin-Sánchez, J; Aguyé, A; Moreno, N; Cooper, C; Díez-Pérez, A; Dennison, E (2014)
UNLABELLED: Temporal trends in hip fracture incidence have recently been reported in some developed countries. Such data in Spain has previously been incomplete; this study reports the stratified incidence of hip fractures in people over 65 in Spain during the last 14 years. INTRODUCTION: The main objective is to establish whether temporal trends in hip fracture incidence in Spain exist. METHODS: Ecological study with data from hospital discharges nationwide. The study includes patients aged ≥ 65 years during a 14-year period (1997-2010). The analysis compares two periods of four years: 1997-2000 (P1) and 2007-2010 (P2). RESULTS: There were 119,857 fractures in men and 415,421 in women. Comparing periods (P1 vs P2) over 10 years, the crude incidence rate/100,000 inhabitant/year increased an average of 2.3%/year in men and 1.4% in women. After adjustment, the rate increased an average of 0.4%/year in men (p < 0.0001), but decreased 0.2%/year in women (p < 0.0001). In men, younger than 85, the decrease was not significant except in 70-74 years, and from 80 years, the adjusted rate increases significantly (p < 0.0001). In women under 80 years of age, the decrease in adjusted rate was significant; there was no change in 80-84 years, and the adjusted rate increased significantly in individuals 85 years and older (p < 0.0001). Mortality rates declined by 22% in both sexes, and the index of overaging population rises 30.1 % in men and 25.2% in women. CONCLUSIONS: This study supports other international studies by showing changes in the incidence of hip fractures after age-population adjustment, which denotes a decrease in the younger age groups and among women and shows an increase in both groups over 85 years. The increase in the crude incidence rate of hip fracture in Spain reflects changes in population structure.